Using a New General Complex Integral Transform for Solving Population Growth and Decay Problems - Mehdi, Sadiq A.; Kuffi, Emad A.; Jasim, Jinan A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
The Population growth and decay issues are one of the most pressing issues in many sectors of study. These issues can be found in physics, chemistry, social science, biology, and zoology, among other subjects. We introduced the solution for these problems in this paper by using the SEJI (Sadiq- Emad- Jinan) integral transform, which has some mathematical properties that we use in our solutions. We also presented the SEJI transform for some functions, followed by the inverse of the SEJI integral transform for these functions. After that, we demonstrate how to use the SEJI transform to tackle population growth and decay problems by presenting two applications that demonstrate how to use this transform to obtain solutions. Finally, we conclude that the SEJI transform can readily solve the problems of population increase and decay, and that the action of this integral transform in overcoming these challenges can be explained through applications.